Investigating the experience of individuals with comorbid posttraumatic stress disorder and substance misuse attending a Seeking Safety group. Issue 1 (7th December 2021) - Airdrie, Jac Neirin; Lievesley, Alexandra; Griffith, Emma
Abstract : Purpose: There is no specific recommended treatment for the co-morbid presentation of post-traumatic stress disorder (PTSD) and substance use disorder in the United Kingdom (UK). Seeking Safety (SS), a group-based treatment that targets symptoms of both disorder, has emerging evidence in the USA but lacks evidence from UK-based samples. The purpose of this study was to explore UK service users' experience of attending SS and evaluate its impact on mental health symptomology and substance misuse. Design/methodology/approach: A mixed method approach was used to evaluate the acceptability of SS for a small sample ( n = 7) of adult users of a substance misuse service in the UK. Thematic analysis was used to explore their experiences, derived from individual semi-structured interviews. The authors also calculated the number of participants who achieved reliable and/or clinically significant change in mental health symptomology and substance misuse from data routinely collected by the service. Findings: Seven overarching themes emerged: strengthening the foundations of the self, the evocation and management of emotions, safety and validation provided relationally, readiness and commitment, content and delivery, Seeking Safety is Not an Island and ending. Most participants with data available both before and after the group made reliable (three out of four) and clinically significant (two out of three) change for depression and anxiety symptomology; however, this was less evident for PTSD symptomology with two out of three making reliable change and one out of three making clinically significant change. Originality/value: To the best of the authors' knowledge, this was the first study exploring the experiences of UK attendees of a SS group as an approach to treating comorbid PTSD and substance misuse.